2018
DOI: 10.1186/s12917-018-1564-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of non-albicans Candida species recovered from mycotic mastitis of cows in Yinchuan, Ningxia of China

Abstract: BackgroundCandida spp. is the vital pathogen involved in mycotic mastitis of cows. However the epidemiology and infection of Candida species in mycotic mastitis of cow in Ningxia province of China has not been explored. In the present study, the epidemiology, antimicrobial susceptibility and virulence-related genes of non-albicans Candida (NAC) species were investigated.MethodsA total of 482 milk samples from cows with clinical mastitis in four herds of Yinchuan, Ningxia were collected and used for the isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 38 publications
(45 reference statements)
3
40
0
1
Order By: Relevance
“…3.3-3.7). Bovine mastitis due to yeasts especially Candida spp has been reported elsewhere (Du et al, 2018). IMIs caused by yeasts are linked to treatment against other IMI pathogens, cross infection from contaminated syringes and cannulas and or contaminated antibiotic preparations (Dworecka-Kaszak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…3.3-3.7). Bovine mastitis due to yeasts especially Candida spp has been reported elsewhere (Du et al, 2018). IMIs caused by yeasts are linked to treatment against other IMI pathogens, cross infection from contaminated syringes and cannulas and or contaminated antibiotic preparations (Dworecka-Kaszak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…3-7). Bovine mastitis due to yeasts especially Candida spp has been reported elsewhere (Du et al, 2018). IMIs caused by yeasts are linked to treatment against other IMI pathogens, cross infection from contaminated syringes and cannulas and or contaminated antibiotic preparations (Dworecka-Kaszak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…131,132 C. krusei has been also found infecting the tonsils, where only surgical removal of the organ offered a permanent cure, causing septic arthritis, ulcers, urinary tract infections, and vasculitis [133][134][135][136] In veterinary, this organism can also cause infections and deteriorate the health conditions in animals. C. krusei was reported as the causative agent of bovine bronchopneumonia and mastitis in Japan, China, Turkey, Algeria, Canada, Polony, and the United Kingdon; [137][138][139][140][141][142][143] while in cats could be responsible for the failure of long-term gastrostomy tubes. 144 For the case of bovine mastitis, it has been suggested that wheat silage, rather than unappropriated milking is the source of the C. krusei cells affecting the udder.…”
Section: Recent Understanding Of the Host-pathogen Interaction Virulementioning
confidence: 99%
“…Fluconazole is one of the most common antifungal drugs used for empirical treatment of candidiasis; however, C. krusei is a species intrinsically resistant to this drug, with more than 95% of clinical and veterinary isolates being fluconazole-resistant. 141,165 The mechanisms behind this observation are not fully understood yet, but the flux pump activity of the ATP-binding cassette transporter Abc1 and reduced fluconazole affinity to Erg11 have been associated with this phenotypic trait. 165,166 It has been also proposed that both proteins could be part of the resistance mechanisms observed in some itraconazole-resistant strains.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation